Analisis Pengelolaan Alokasi Dana Desa Di Desa Makkawaru Kecamatan Mattiro Bulu Kabupaten Pinrang - Ramadani, Mutiara; Hamzah, Hajrah; Harianto, Dedi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the management of Village Fund Allocation (ADD) in Makkawaru Village based on indicators in Permendagri Number 20 of 2018. This study uses a qualitative descriptive approach. Data collection techniques are carried out through interviews and documentation with village officials and financial documents. The research results show that the management of Village Fund Allocation (ADD) in Makkawaru Village has gone through five stages: planning, implementation, administration, reporting, and accountability, which have largely complied with regulations. However, deficiencies were still found at the reporting stage, such as incomplete documentation and incompletely detailed recording evidence. In terms of transparency, the village government has attempted to provide information through notice boards and realization banners. Overall, the management of Village Fund Allocation (ADD) in Makkawaru Village is fully compliant with regulations and still needs improvement in terms of administration, reporting, and information transparency.